The shifting roles of medical stakeholders in opioid substitution treatment: a comparison between Denmark and the UK. Issue 4 (7th December 2015) - Bjerge, Bagga; Duke, Karen; Frank, Vibeke Asmussen
Abstract : Purpose: – The purpose of this paper is to examine the shifting roles of medical professionals as stakeholders in opioid substitution treatment (OST) policies and practices in Denmark and the UK within the past 15 years. Design/methodology/approach: – The paper is based on literature reviews, documentary analyses and key informant interviews with a range of stakeholders involved in OST and policy in Denmark and UK. The study is part of the EU-funded project: Addictions and Lifestyles in Contemporary Europe: Reframing Addictions Project. Findings: – Denmark and the UK are amongst those few European countries that have long traditions and elaborate systems for providing OST to heroin users. The UK has a history of dominance of medical professionals in drugs treatment, although this has been recently challenged by the recovery movement. In Denmark, a social problem approach has historically dominated the field, but a recent trend towards medicalisation can be traced. As in all kinds of policy changes, multiple factors are at play when shifts occur. We examine how both countries' developments around drugs treatment policy and practice relate to broader societal, economic and political changes, how such divergent developments emerge and how medical professionals as stakeholders enhanced their roles as experts in the field through a variety of tactics, including the production and use of "evidence", which became a key tool to promote specific stakeholder's perspectives in these processes. Originality/value: – The paper contributes to current policy and practice debates by providing comparative analyses of drug policies and examination of stakeholder influences on policy processes.